2000
DOI: 10.1002/(sici)1097-0207(20000420)47:11<1807::aid-nme819>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of thermal processes using an Eulerian formulation and application in laser surface hardening

Abstract: SUMMARYA systematic design approach has been developed for thermal processes combining the ÿnite element method, design sensitivity analysis and optimization. Conductive heat transfer is solved in an Eulerian formulation, where the heat ux is ÿxed in space and the material ows through a control volume. For constant velocity and heat ux distribution, the Eulerian formulation reduces to a steady-state problem, whereas the Lagrangian formulation remains transient. The reduction to a steady-state problem drastical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 25 publications
0
12
0
1
Order By: Relevance
“…Note that this steady‐state description is suitable for problems with a stationary regime reached throughout the process, like welding (eg, other work). In addition, the solutions are solved in trueΩ˜, where BCs are not defined and should be chosen in an appropriate way to well approximate original solutions in the fixed frame.…”
Section: Application To Space‐time Computational Vademecum For Nonlinmentioning
confidence: 99%
“…Note that this steady‐state description is suitable for problems with a stationary regime reached throughout the process, like welding (eg, other work). In addition, the solutions are solved in trueΩ˜, where BCs are not defined and should be chosen in an appropriate way to well approximate original solutions in the fixed frame.…”
Section: Application To Space‐time Computational Vademecum For Nonlinmentioning
confidence: 99%
“…For a quasi-steady state problem, the transient heat transfer analysis of equation (1) reduces to a boundary value problem in an Eulerian frame [37][38][39][40] …”
Section: Thermal Analysismentioning
confidence: 99%
“…Its nodal values on a particular element at time t are given by a 3 × m matrix (10) In this study, the nodal velocities…”
Section: Space-time Finite Elementmentioning
confidence: 99%
“…Rajadhyaksha and Michaleris [10] proposed an Eulerian finite element formulation, to optimize a quasi-static thermal process using a SUPG formulation. They concluded that an Eulerian formulation can drastically reduce the computational run-time, and then can be applied to the optimization of quasistate processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation